2021
DOI: 10.3390/cancers13112728
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of MRI Melanin Quantification and Cytogenetic Abnormalities in Liver Metastases of Uveal Melanoma

Abstract: To evaluate the prognostic implications of melanin quantification assessed by magnetic resonance imaging (MRI) with respect to the clinical, pathological, and genetic features of liver metastases of uveal melanoma (LMUM). This single-center retrospective cohort study included 63 patients eligible for margin-free resection of LMUM between 2007 and 2018. Comparative genomic hybridization of resected liver metastases on microarrays was performed for genetic risk classification. Metastases exhibiting monosomy 3 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Melanin content is shown to correlate with hyperintensity on T1-weighted imaging, meaning that the signal intensity of melanoma may be determined by the amount of melanin within the lesion. 24 We hypothesized that there was not much melanin in the present case, which would explain why the T2-weighted imaging showed a slightly higher signal rather than the typical low signal. Based on the pre-treatment suggestive diagnosis, exhaustive screening with particular attention to the skin, eyes, anorectum and vagina, and general radiological examination, could be arranged to avoid the omission of another primary melanocytic cancer and contribute to formulating an optimal therapeutic regimen.…”
Section: Discussionmentioning
confidence: 70%
“…Melanin content is shown to correlate with hyperintensity on T1-weighted imaging, meaning that the signal intensity of melanoma may be determined by the amount of melanin within the lesion. 24 We hypothesized that there was not much melanin in the present case, which would explain why the T2-weighted imaging showed a slightly higher signal rather than the typical low signal. Based on the pre-treatment suggestive diagnosis, exhaustive screening with particular attention to the skin, eyes, anorectum and vagina, and general radiological examination, could be arranged to avoid the omission of another primary melanocytic cancer and contribute to formulating an optimal therapeutic regimen.…”
Section: Discussionmentioning
confidence: 70%
“…Interesting results have been obtained by assessing the colouration of uveal melanoma and cutaneous melanoma metastases to the liver. These studies found that uveal melanoma metastases showed higher pigmentation scores than cutaneous melanoma metastases, and the level of pigmentation was correlated with different clinical outcomes [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, magnetic resonance imaging studies of uveal melanoma and its metastases show that the tumour may have a heterogeneous internal structure in terms of melanin content, which in the clinical picture translates into the presence of varying degrees of pigmentation throughout the tumour volume. The authors of this study claim that most tumours (>80%) are nevertheless homogeneous in terms of melanin content throughout the volume [ 62 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is known as a useful tool in cases of untransparent lens or subretinal effusion because the MR appearance of UM mainly depends on the melanin content (52). UM typically displays a high signal intensity in T1-weighted images and a low signal intensity in T2-weighted images (53).…”
Section: Discussionmentioning
confidence: 99%